The Importance of Studying the Life and Work of Uzbek Composers in Music Classes of General Education Schools - Dilorom Tursunova (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Melodies and songs of master composers can easily compete with the musical works of the world's peoples who have a professional high musical culture with their logical clarity and level of philosophical observation, complete and deep content. In the article, the author highlighted the importance of studying the life and work of Uzbek composers in music classes of general education schools.